(untitled) (Annals of Medical Research, 2021)
Aim: Pathologic evaluation of rectal cancer is very important. Lymph node yields may be related to surgical technique or inadequate harvesting in the pathology department. The importance of lymph node yields >12 have been emphasized by many researchers to be adequate for staging. In stage II rectal cancer, the impacts of lymph node yield on locoregional recurrence and patient survival have not been studied. The aim of the present study is to evaluate the impact of lymph node yield on outcome and prognosis of the patients with stage II rectal cancer. Material and Methods: Patients with stage II rectal cancer who were operated in our institution between 2008 and 2013 were retrospectively analyzed to determine the impact of lymph node yield on survival, locoregional and distant metastasis.Results: Overall, local and distant recurrence rates were 13.9%, 4.65% and 9.30%; respectively. We did not find any significant difference in terms of locoregional and distant metastasis rates among Group I (lymph node12) (p>0.05). The 5-year survival of the patients in Group 1 versus Group 2 were 86.7% versus 82%; respectively (p>0.05). Conclusions: Results of the present study emphasize that lymph node yields may not have an impact on patient survival or recurrence. However, the patient groups were heterogeneous and the volume was low, therefore, more studies with higher volumes are needed. Keywords: Rectal Cancer; Staging; Lymph Node Metastasis.